Balancing Passion and Prospects: How Personal Aspirations and Job Market Trends Influence the Academic Programme Selection Among Students - Ibrahim, Mohammed Gunu; Mohammed, Siibaway; Boapeah, Clementina Okyere (Advances in Social Sciences Research Journal, 2025)
Selecting academic programmes at the undergraduate level is a critical decision that defines students’ future careers and general well-being. This study aims to explore the influence of personal aspirations and labour market trends on the choice of academic programmes at the undergraduate. The study was rooted in the Situated Expectancy-Value Theory and Human Capital theory to understand how personal and labour market trends influence academic programme decision-making. The study employed a case study design and used a convergent-parallel mixed-methods approach to collect data from 379 students through structured questionnaires and 20 qualitative data through semi-structured interviews. The findings of the study revealed that passion for a course, personal fulfilment, and peer influence are the most dominant personal factors, while future employment opportunities, job security, expected income as well and opportunities for international mobility are the labour market-related factors that strongly shape programme choice among undergraduate students. The results show that programme selection among undergraduate students is not purely driven by passion or market-labour market trends, but a balance between intrinsic motivations and external market realities. The study highlights the need to strengthen career guidance systems, curriculum design that combines passion with employability, and higher education policy that takes into consideration the labour market demands and the personal aspirations of students.